2015
DOI: 10.1007/s11130-015-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation and Subsequent Pasteurization Processes on Amino Acids Composition of Orange Juice

Abstract: The fermentation of fruit produces significant changes in their nutritional composition. An orange beverage has been obtained from the controlled alcoholic fermentation and thermal pasteurization of orange juice. A study was performed to determine the influence of both processes on its amino acid profile. UHPLC-QqQ-MS/MS was used for the first time for analysis of orange juice samples. Out of 29 amino acids and derivatives identified, eight (ethanolamine, ornithine, phosphoethanolamine, α-amino-n-butyric acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
14
1
1
Order By: Relevance
“…Interestingly, the application of HTST heat treatment is reported to increase: (1) total phenolics, (−)‐epicatechin, ferulic acid, and p ‐coumaric acid content in apricot nectar (Huang and others ); (2) color hue in lemon/pomegranate juice blend (Mena and others ); (3) nutritional value in fermented orange juice (Cerrillo and others ); and (4) viscosity in carrot juice (Chen and others ) and mango nectar (Liu and others ). Nevertheless, the exposure to high temperatures, even for short periods, can result in sensorial changes of appearance, texture, color, and flavor (Miller and Silva ).…”
Section: Thermal Treatmentsmentioning
confidence: 99%
“…Interestingly, the application of HTST heat treatment is reported to increase: (1) total phenolics, (−)‐epicatechin, ferulic acid, and p ‐coumaric acid content in apricot nectar (Huang and others ); (2) color hue in lemon/pomegranate juice blend (Mena and others ); (3) nutritional value in fermented orange juice (Cerrillo and others ); and (4) viscosity in carrot juice (Chen and others ) and mango nectar (Liu and others ). Nevertheless, the exposure to high temperatures, even for short periods, can result in sensorial changes of appearance, texture, color, and flavor (Miller and Silva ).…”
Section: Thermal Treatmentsmentioning
confidence: 99%
“…Besides, Cerrillo et al . () observed an increase of lysine in alcoholic fermentation, whilst histidine did not have a significant change in its concentration. The rest of variables associated to final samples according to the loadings, such as glutamic acid, isoleucine and phenylalanine, had a trend to rise after gluconic acid fermentation, although their concentrations did not have a significant increase (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, Cerrillo et al . () showed that the initial concentration of amino acids was similar after alcoholic fermentation of orange juice had finished. Besides, Álvarez‐Fernández et al .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Sereewatthanawut et al [34] have said that, with increasing temperature, some amino acids are degraded to form low molecular weight carboxylic acids such as formic, acetic, and propionic acids, resulting in a reduction of the total amino acid concentration. On the other hand, in fermented orange juice, the amino acid profile, including citrulline, was not modified by pasteurization (85 ∘ C for 30 s); however, the fermentation time (9 days) significantly increased the total amino acid content [35].…”
Section: Citrulline Contentmentioning
confidence: 92%